Pengaruh Promosi Jabatan dan Remunerasi Terhadap Kepuasan Kerja Personil Satuan Sabhara Polres Tasikmalaya Kota - Hendi Herdiansyah; Aini Kusniawati; Ading Rahman Sukmara (Pajak dan Manajemen Keuangan, 2024)
The problems faced in this study include (1) How does promotion affect the job satisfaction of Tasikmalaya City Police Sabhara Unit Personnel? (2) What is the effect of remuneration on job satisfaction of Tasikmalaya City Police Sabhara Unit Personnel? (3) What is the effect of promotion and remuneration on job satisfaction of Tasikmalaya City Police Sabhara Unit Personnel? This study aims to study, know, and analyze (1) The effect of job promotion on job satisfaction of Tasikmalaya City Police Sabhara Unit Personnel. (2) The effect of remuneration on the job satisfaction of Tasikmalaya City Police Sabhara Unit Personnel. (3) The effect of position promotion and remuneration on job satisfaction of Tasikmalaya City Police Sabhara Unit Personnel. The method used in this study is explanatory survey, while the technical data analysis is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Position promotion has a positive effect on job satisfaction in the Personnel of the Tasikmalaya City Police Sabhara Unit. This means that if the promotion of the position is increased, then job satisfaction in the Tasikmalaya City Police Sabhara Unit Personnel will also increase. (2) Remuneration has a positive effect on job satisfaction in the Personnel of the Tasikmalaya City Police Sabhara Unit. This means that if the remuneration is increased, then job satisfaction in the Tasikmalaya City Police Sabhara Unit Personnel will also increase. (3) Position promotion and remuneration have a positive effect on job satisfaction in the Personnel of the Tasikmalaya City Police Sabhara Unit. This means that if position promotions and remuneration are increased, job satisfaction in the Tasikmalaya City Police Sabhara Unit Personnel will also increase.